The Effect of Enviromental Social Governance (ESG), Audit Quality and Corporate Risk on Tax Avoidance (Case Study of Manufacturing Companies listed on the IDX for the 2021-2023 Period) - Vera Puji Lestari; Baihaqi Baihaqi (Utan Kayu Publishing, 2025)
This study aims to analyze the effect of Environmental Social Governance (ESG), audit quality, and company risk on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. This study uses secondary data in the form of annual reports and sustainability reports obtained through purposive sampling method. The results showed that the three independent variables, namely ESG, audit quality, and corporate risk, had a significant influence on tax avoidance. ESG has no effect on tax avoidance, which states that companies with high ESG disclosure can still legally perform tax avoidance. Audit quality has a negative effect, indicating that the involvement of a quality Public Accounting Firm (KAP) can suppress tax avoidance practices. Meanwhile, company risk has a positive effect on tax avoidance, indicating that companies with a high level of operational or financial risk tend to reduce their tax burden as an efficiency strategy. These findings provide implications for regulators, investors, and stakeholders in formulating tax policies and corporate governance that are more accountable and sustainable.